Staphylococcus aureus in rural drinking water. - LeChevallier, M W (1980)
Coagulase-positive Staphylococcus aureus was isolated from over 6% of 320 rural drinking water specimens. Well water was the most common source examined. The presence of S. aureus was not found to correlate with the presence of coliform bacteria. Strains of Staphylococcus that produced enterotoxin A were found in 40% of the samples containing S. aureus. Additional studies showed that faucet aerator screens were common sources of high cell densities of S. aureus.